Problems in the current diagnostic standards of clinical N1 non-small cell lung cancer. Issue 6 (16th November 2007) - Hishida, T; Yoshida, J; Nishimura, M; Nishiwaki, Y; Nagai, K
Abstract : Background: Although clinical N1 (cN1) non-small cell lung cancer (NSCLC) is considered to be locoregional, the postoperative outcome is disappointing, with a 5 year survival of less than 50%. One possible reason may be that cN1disease diagnosed by current standard imaging modalities often contains unexpected N2 disease. This study was conducted to evaluate the surgical and pathological results of patients with cN1 NSCLC. Methods: Among 1782 patients with NSCLC who underwent intended curative resection from 1993 to 2003, 143 patients were identified as having cN1 disease and were enrolled in this study. The clinicopathological records and CT films of each patient were retrospectively reviewed to identify predictors for pN2–3 disease. Results: The pathological nodal status was pN0 in 23% (n = 33), pN1 in 47% (n = 67) and pN2–3 in 30% (n = 43) of patients. Patients with pN2–3 showed a significantly worse 5 year survival rate of 38% compared with patients with pN0 (68%) and pN1 (60%) (p = 0.017 and 0.007, respectively). Multivariate analysis showed that adenocarcinoma histology was a significant predictor for pN2–3 disease (OR 3.312, 95% CI 1.439 to 7.784; p = 0.005). The presence of N1 node separate from the main tumour on CT scans tended to predict pN2–3 disease although this did not reach statistical significance (OR 2.103, 95% CI 0.955 to 4.693; p = 0.066). Pathological N2–3 disease was found in 53% of patients with adenocarcinoma with a separate N1 pattern and in only 12% of patients with non-adenocarcinoma with a continuous N1 pattern. Conclusions: The diagnosis of N1 status by contrast enhanced CT scans is unsatisfactory with a high rate of unexpected pN2 disease. To avoid infertile lung resection, patients with CT diagnosed N1 adenocarcinoma, especially with a separate N1 pattern on CT, should be considered for additional invasive node biopsy modalities, including mediastinoscopy.